2017
DOI: 10.3892/ol.2017.6466
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic evaluation of tumor-associated macrophage density and vessel inflammation in invasive breast carcinomas

Abstract: Tumor-associated macrophages (TAMs) are major constituents of the tumor microenvironment in solid tumors and have been implicated as mediators of tumor progression, invasion and metastasis. Correspondingly, accumulation of TAMs is associated with unfavorable clinical outcomes in numerous types of solid tumors. E-selectin is a hallmark of inflammation and a key adhesion molecule that accommodates the initial contact of circulating immune cells with the inflamed vessel surface. Currently, the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…For example, TAMs can process cleavable ADCs through FcRgmediated interactions to produce free drug, resulting in antitumor activity (42). Indeed, we saw an abundance of TAMs within the necrotic core of these tumors, which is a common feature of solid tumors (40,50), and one which may enable release of free drug because we show that antibody-bound dead cells are internalized by macrophages in vitro. Others have indicated that the release of reducing agents by dead tumor cells can cleave disulfide linkers (45), which may be one mechanism by which DAB4-ADC with disulfide linkers are cleaved independently of internalization.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, TAMs can process cleavable ADCs through FcRgmediated interactions to produce free drug, resulting in antitumor activity (42). Indeed, we saw an abundance of TAMs within the necrotic core of these tumors, which is a common feature of solid tumors (40,50), and one which may enable release of free drug because we show that antibody-bound dead cells are internalized by macrophages in vitro. Others have indicated that the release of reducing agents by dead tumor cells can cleave disulfide linkers (45), which may be one mechanism by which DAB4-ADC with disulfide linkers are cleaved independently of internalization.…”
Section: Discussionmentioning
confidence: 72%
“…For the LL2 cells, SG3199 was the most potent with an IC 50 of 1 pmol/L, followed by Duocarmycin DM (142 pmol/L) and MMAE (687 pmol/L) compared with 1.5 mmol/L for cisplatin. Although A549 cells were more resistant, SG3199 was also the most potent inhibitor of A549 cell survival (IC 50 16 pmol/L), followed by duocarmycin DM, MMAE, and cisplatin (IC 50 399 pmol/L, 844 pmol/L, and 6.8 mmol/L respectively; Fig. 4A).…”
Section: Effect Of Free Drugs On Cell Survivalmentioning
confidence: 98%
“…24,25 Several studies have reported that CCL2 and the inflammatory environment promote the malignant behavior of different tumors. [26][27][28] Xu et al found that CCL2 recruits monocytes to the TME and polarizes macrophages into the M2 type. 25 Secretion of CCL2 is also an important manifestation of TAM polarization in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…For example, similar to the finding in this study that metastatic ccRCC exhibited higher expression of CD163, it was reported that high CD163 expression in the adipose stroma of breast cancer independently predicted shorter cancer-specific survival [210]. However, unlike the result in another study based in the US, which found a prognostic potential for CD68 in discriminating invasive (high expression) and benign (low expression) breast tumours [213], CD68 expression levels in the perinephric adipose tissue in this present study did not show any discriminative potential for metastatic and non-metastatic ccRCC. The discrepancy may be due to different quantification methods: subjective semi-quantitative evaluation was applied in the previous study, whereas objective digital quantification was applied in this present study based on three thresholding.…”
Section: Discussionsupporting
confidence: 83%